Consensus on the management of traumatic brain injury in older adults: Results from a Delphi study - Lagares, Alfonso; Depreitere, Bart; Marklund, Niklas; Castano; Leon; Ana.María; Posti, Jussi P.; Younsi, Alexander; Klein, Sam; EANS Neurotrauma and Critical Care Section and expert panel members (Elsevier BV, 2026)
Introduction
As the world population is rapidly becoming older, the incidence of traumatic brain injury (TBI) is increasing among older adults with vast implications for brain health of older adults in Europe. Due to differences from younger patients, there are areas of uncertainty in the assessment, diagnosis and management of TBI in older adults.
Research question
To reach a consensus among experts on statements regarding the definition of old age, assessment, diagnosis and management of traumatic brain injury in older adults.
Materials and methods
A modified Delphi method consisting of two online rounds was organised, followed by an in-person meeting. Consensus was defined as >75 % agreement. In the second online round the experts were able to view their first assessment and the average of the group. Some statements were rephrased and presented again in the in-person meeting. Questions with numerical data could not be assessed by consensus and descriptive and non-parametric statistics were used to analyze them.
Results
Experts (n = 72), from different nationalities (Europe, United States, Latin America, Africa and Asia) and specialities (Neurosurgery, Emergency Medicine, Intensive care medicine) responded on 62 statements. Consensus was finally reached on 44 statements regarding the definition of older adulthood, as well as the assessment, surgical and intensive care management, discharge, and rehabilitation of patients.
Discussion and conclusions
This consensus reinforces the importance of this area for physicians and researchers interested in traumatic brain injury. It signals important areas of agreement as well as future topics for research and specific knowledge gaps.